Application of Neuroscience Tools in Building Construction – An Interdisciplinary Analysis - Wang, Mengmeng; Liu, Xiaodan; Lai, Yu; Cao, Wenna; Wu, Zhiyong; Guo, Xiaotong (Frontiers in Neuroscience, 2022)
Interdisciplinary integration is a new driving force for the development of science and technology. Neuroscience, as a powerful tool for studying human physiology and psychology, has generated interdisciplinary crossover with the field of building construction and has received wide attention from scholars in this field. In this paper, a systematic review of the interdisciplinary applications of neuroscience tools using bibliometric methods is conducted, and it has been found that the built environment, construction safety, architectural design, and occupational health are the main research directions, and thermal comfort, air quality, hazard recognition, safety training, aesthetic design, and biophilic design, etc. are the most frequently studied topics for the application of neuroscience tools. Currently eye tracking and electroencephalogram are most used in the field of building construction, while functional near-infrared spectroscopy, functional magnetic resonance imaging and trigeminal nerve stimulation are still in its initial stage of application.neuroscience tools in building construction